Fungal diversity associated to the olive moth, prays oleae Bernard : a survey for potential entomopathogenic fungi - Oliveira, Ivo Vaz (2012)
Olive production is one of the main agricultural activities in Portugal. In the region of Trás-os-Montes this crop has been considerably affected by Prays oleae. In order to evaluate the diversity of fungi on P. oleae population of Trás-os-Montes olive orchards, larvae and pupae of the three annual generations (phyllophagous, antophagous and carpophagous) were collected and evaluated for fungal growth on their surface. From the 3828 larvae and pupae, a high percentage of individuals exhibited growth of a fungal agent (40.6%), particularly those from the phyllophagous generation. From all the moth generations, a total of 43 species from 24 genera were identified, but the diversity and abundance of fungal species differed between the three generations. Higher diversity was found in the carpophagous generation, followed by the antophagous and phyllophagous generations. The presence of fungi displaying entomopathogenic features was highest in the phyllophagous larvae and pupae, being B. bassiana the most abundant taxa. The first report of B. bassiana presence on P. oleae could open new strategies for the biocontrol of this major pest in olive groves, since the use of an already adapted species increases the guarantee of success of a biocontrol approach. The identification of antagonistic fungi able to control agents that cause major olive diseases, such as Verticillium dahliae, will benefit future biological control approaches for limiting this increasingly spreading pathogen.